Penerapan Model Pembelajaran Picture and Picture Berbantuan Media Gambar Komik Dalam Meningkatkan Keterampilan Menulis Karangan Narasi di Sekolah Dasar - Yulistia; Neneng Sri Wulan; Hisny Fajrussalam (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
In Indonesian language learning, there are four aspects of language skills that are developed, namely, listening, speaking, reading, and writing. All four aspects are important and needed. One aspect of language skills taught at school is writing skills. This study was motivated by the low writing skills of fifth grade students. This research was conducted at SDN Kaumpandak 02 with 21 research subjects. The purpose of this research is to improve learning activities so that there is an increase in teacher and student activities and improve the results of grade V students' skills in writing narrative essays by applying the Picture and Picture learning model. The type of research used in this study is class action research. Based on the results of the average acquisition that has been known, at the pre-cycle stage students obtained an average score of 57.85. Cycle I students obtained an average score of 67.47 with 8 students who completed learning, while 13 students who did not complete learning. Cycle II students obtained an average score of 76 with a total of 15 students who completed learning, while 6 students who did not complete learning. It can be concluded that the application of Picture and Picture learning model assisted by comic image media can improve students' narrative essay writing skills.